Sequestering carbon without reducing food production: The role of recirculating aquaculture systems - Morello, Thiago; Gadanakis, Yiorgos; Gonzalez, Jorge Campos; Mancini, Mattia; Howe, Keith; Tingley, Diana; Manchi, Rajesh; Sanders, Trystan; Wilson, Rod; Bateman, Ian J. (My University, 2025)
The annual creation of 30,000 ha of woodland, a key component of UK's net-zero GHG emissions strategy, may drive countries exporting food to Great Britain (GB) to increase their emissions, an example of international carbon leakage. This can be mitigated by intensifying British domestic food production and our objective is to assess the viability of an intensification based on recirculating aquaculture systems (RAS), a land-saving technology recycling its own water. We built a computational partial equilibrium model whose supply side extended positive mathematical programming to aquaculture at grid-cell level. Agricultural censuses were combined with RAS financial data from a British research and business impact project. Results revealed that RAS was viable in 1.6 % of GB's farmland, substituting 28 % of current annual warmwater prawn imports. The implementation of GB's annual woodland creation goal also proved viable for farmers, but it induced, by shifting 0.2 % of agricultural area into woodland, a 0.007 % drop in food production, what would lead to international carbon leakage. RAS mitigated leakage completely and its contribution to food production was even larger when powered by anaerobic digesters. A lower interest rate charged on loans for RAS also boosted food production, which demonstrates financial sector's role in leakage mitigation.
Keywords: Carbon leakage; Afforestation; Recirculating aquaculture systems; Positive mathematical programming; Partial equilibrium; Agriculture